Effect of futsal student activity unit participation on physical fitness among university students - Arif Fajar Prasetiyo; Sopyan Rizki Haryadi; Dadan Pra Rudiana; Tini Martini (Universitas Suryakancana, 2026)
Physical fitness plays a significant role in promoting health, enhancing productivity, and enabling students to effectively engage in their daily academic responsibilities. Nevertheless, university students often experience a decline in physical activity due to their largely sedentary routines and the growing reliance on digital technology. To counter this trend, one viable approach is to encourage student involvement in sports activities organized by student organizations, such as the Futsal Student Activity Unit (UKM). The objective of this study was to evaluate the impact of participation in the Futsal Student Activity Unit on enhancing physical fitness among students at Universitas Subang. This research utilized a quantitative methodology with a pre-experimental framework, specifically a one group pretest-posttest design. The sample consisted of 30 students who engaged actively in the futsal UKM events. Data collection involved conducting physical fitness assessments both prior to and following the training program, which included evaluations of cardiorespiratory endurance along with other fitness components. The analysis of the data was conducted using descriptive statistics and a paired sample t-test to identify any differences between the pretest and posttest outcomes. The findings demonstrated that engaging in futsal activities positively influenced the physical fitness levels of the students. Those who participated consistently in futsal training exhibited improvements in their fitness after the intervention. In summary, participating in the Futsal Student Activity Unit can effectively enhance the physical fitness of university students and serves as a valuable strategy for fostering active lifestyles within higher education settings.